Integration of Religious Values in Higher Education Curriculum - Yeni Ayu Masruroh; Nayshela Fransiska; M. Rasya Pratama; Azura Bintang; Eva Iryani (Fakultas Agama Islam, 2026)
The integration of religious values into the higher education curriculum has become a critical issue in the development of higher education in the modern era, particularly amid rising moral degradation, intolerant attitudes, and the dominance of an educational orientation that tends toward materialism. Higher education institutions are expected not only to produce academically outstanding graduates but also to foster religious character, moral integrity, and the ability to maintain social harmony within a multicultural society. This study aims to analyse the integration of religious values in higher education curriculum design, its implementation in teaching and academic culture, and its contribution to character formation and religious moderation among students. The research employs a qualitative approach using a literature review (library research). Data were obtained from scientific journals, academic books, and relevant educational policy documents, then analysed using descriptive-analytical content analysis techniques. The results indicate that the integration of religious values is achieved through the development of interdisciplinary curricula, the strengthening of a religious academic culture, and the internalization of religious moderation values within the learning process. This integration has proven effective in shaping students’ character to be disciplined, tolerant, and socially responsible. This study implies the importance of developing a holistic and integrative higher education curriculum to produce graduates who are not only intellectually competent but also morally and spiritually mature.